Assessment of the regulatory systems of the body of children in the early childhood - Ryspaeva, G.K.; Tykezhanova, G.M. (Pub KSU, 2016)
The assessment of the regulatory systems of the body of children in the early childhood was conducted by using physiological and clinical examination in junior classes of secondary school. Morphological and functional development of children was evaluated in terms of height, body weight, cardiovascular system was assessed by changes in heart rate, SBP, DBP, PP, ECG, systolic blood volume (SV) and blood oxygenation. State of regulatory systems was measured by heart rate variability (HRV), analyzing the common basic parameters of cardiointervalography: M, IC, Mo, Amo, VR and their derivative indicators by R.M.Baevsky: VIR (vegetative index rate), VBI (vegetative balance index), SI (index of regulatory systems stress) ARP (adequacy of regulation processes).
Төменгі сынып мектеп балалары ағзасының реттеуші жүйелері жағдайын бағалау
Оценка состояния регуляторных систем организма у детей младшего возраста
Keywords: adaptation; heart rate variability; vegetative parameters rhythm performance; heart rate; parasympathetic mechanisms sympathetic influence